Prospective teachers’ attitudes towards using Indonesian in English classes: Does study duration matter? - Subekti Adaninggar Septi; Arrang Judith Ratu Tandi; Kurniawati Lemmuela Alvita; Tulaktondok Linerda (Journal of Language and Cultural Education)
This survey study aimed to investigate the attitudes of Indonesian second/foreign language (L2) learners of English towards the use of Indonesian, learners’ first language (L1), in English class and to see whether learners’ study duration influenced these attitudes. 101 prospective English teachers in their first, second, third, and fourth year of study at the English Language Education department participated in this study. Descriptive statistics revealed that learners held very positive attitudes toward using Indonesian in English classes. Through a chi-square test of independence, it was also found that these attitudes did not significantly differ among learners from different batches. Informed by the findings, pedagogical implications include adjustment of assessments allowing learners to practice L2 more, enhancing exposure to L2 in and outside the class, and conducting confidence-building activities allowing learners to use L2 in a more relaxing environment, minimising fear of making mistakes. Suggested directions for future studies include conducting longitudinal or comparative studies assessing how bilingual instruction or learners' attitudes towards it contribute to learning outcomes. Investigating how these attitudes affect learners' language skills, such as listening and speaking, is also strategic.